Toward a Robust Elastic Geobarometry of Kyanite Inclusions in Eclogitic Diamonds. Issue 8 (15th August 2018) - Nestola, F.; Prencipe, M.; Nimis, P.; Sgreva, N.; Perritt, S. H.; Chinn, I. L.; Zaffiro, G.
Abstract: Here we report the first results from elastic geobarometry applied to a kyanite inclusion entrapped within an eclogitic diamond (from Voorspoed mine, South Africa) using micro‐Raman and Fourier transform infrared spectroscopy, electron microprobe analysis, ab initio calculations, and finite element modeling. Application of elastic geobarometry to very elastically anisotropic kyanite inclusions is challenging, as current models do not allow for elastic anisotropy. In order to minimize the effects of anisotropy, we have explored the effects of deviatoric stress on Raman modes via ab initio density functional theory. The results allowed us to select the Raman mode (at ca. 638 cm −1 ) that is the least sensitive to deviatoric stress. The shift of this band in the inclusion while still trapped within the diamond relative to the inclusion in air (once liberated) was used under hydrostatic approximation to determine a residual pressure on the inclusion of 0.184 ± 0.045 GPa and an entrapment pressure of 5.2 ± 0.3 GPa ( 160 km depth) for an FTIR N‐aggregation residence temperature of 1119 ± 50 °C. This is the first geothermobarometric determination for a diamond from the Voorspoed kimberlite. It overlaps with P–T estimates obtained by traditional chemical geobarometry for diamonds from other kimberlites from the Kaapvaal craton, suggesting that the hydrostatic approximation does not introduce significant errors in the geobarometric evaluation. Our protocol of Raman peak selection can be used for geobarometry of further kyanite‐bearing diamonds and may provide a guide for more robust geobarometry of other types of mineral inclusions in diamonds, both eclogitic and peridotitic. Key Points: Elastic geobarometry applied to kyanite inclusions within diamond provides the pressure and temperature entrapment conditions Eclogitic diamonds from Voorspoed (South Africa) form at 5.2 GPa and 1120 °C In order to minimize the effects of anisotropy, the effects of deviatoric stress on Raman modes via ab initio DFT were explored